Cyclic changes of Asian monsoon intensity during the early mid-Holocene from annually-laminated stalagmites, central China. (1st August 2015) - Liu, Dianbing; Wang, Yongjin; Cheng, Hai; Edwards, R.L.; Kong, Xinggong
Abstract: Climate during the early Holocene was highly variable due to the complex interplay of external and internal forcing mechanisms. The relative importance for them on the Asian monsoon (AM) evolution yet remains to be resolved. Here we present two-to six-yr-resolution oxygen isotope (δ 18 O) records of five stalagmites, four of which are annually-laminated, from Qingtian Cave, central China, revealing detailed AM variability between 10.9 and 6.1 ka BP. Over the contemporaneous periods, the δ 18 O records agree well with each other at multi-decadal to centennial timescales. When pieced together with the previously published isotopic data from the same cave, the final δ 18 O record reveals detailed AM variability from the last deglaciation to the mid-Holocene, consistent with other cave records. The most striking feature of the δ 18 O record is the recurrence of centennial-scale oscillations, especially during the annually-counted period (8.8–6.1 ka BP). Cross-wavelet analyses between the δ 18 O record and solar proxies show strong coherence at 200-yr cycle, suggesting that solar output was actively involved as a primary contributor. The AM depression at 8.2 ka BP is indistinguishable in amplitude and pattern from a series of weak AM events after 8 ka BP. We speculate that these centennial-scale AM changes might be regulated by the positive feedbacks of oceanic/atmospheric interactions to the solar activity under the condition of the retreat of continental ice-sheets. Highlights: A record of 2-yr-resolution Asian Monsoon variability between 8.8 and 6.1 ka B.P. Persistence of centennial Asian monsoon oscillations during the early mid-Holocene. Evidence for a direct sun–climate connection during the early mid-Holocene. New insights into the interplay of the ice-sheets and the tropical ocean on the AM in the early mid-Holocene.